An Adaptive Feedback Mechanism for Consensus Reaching Processes Based on Individuals’ Credibility - Cabrerizo, Francisco Javier; Pérez, Ignacio Javier; Morente-Molinera, Juan Antonio; Alonso, Sergio; Herrera-Viedma, Enrique (Proceedings of the 52ND annual Hawait international conference on system sciences, 2021)
In group decision making, the decision made should be the one of highest consensus. Numerous consensus reaching processes have been developed as a part of the decision process. Within a consensus reaching process, a notable step is that of the feedback mechanism that helps the individuals arrive at an agreement by generating some recommendations on how they should modify their evaluations. Our objective is to present a new feedback mechanism based on individuals' credibility. Different from the existing approaches, it adapts the recommendations provided to the individuals depending on their credibility.
Keywords: group decision-making; model; argumentation; consistency; information; support; WOS(2); Scopus